2007
DOI: 10.1103/physrevb.75.134411
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of the non-Fermi-liquid metalCeRu4Sb12and dense Kondo semiconductorCeOs4Sb12

Abstract: We have investigated elastic properties of the Ce-based filled skutterudite antimonides CeRu 4 Sb 12 and CeOs 4 Sb 12 by means of ultrasonic measurements. CeRu 4 Sb 12 shows a slight increase around 130 K in the temperature dependence of the elastic constants C 11 , ͑C 11 − C 12 ͒ / 2, and C 44 . No apparent lattice softening toward low temperature expected by a quadrupolar response of the 4f-electronic ground state of the Ce ion was observed at low temperatures. On the other hand, CeOs 4 Sb 12 shows a pronoun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…On the other hand, the result obtained by Nakanishi shows a slight increase around 30 K, however, no apparent frequency dependence was found so far. 21 These results probably lead to the absence of rattling in CeOs 4 Sb 12 though the work is still continuing and support the idea that the contribution of conduction electrons is essential for the development of rattling through electron-phonon interaction. Figure 2 displays the temperature dependence of the relative change in elastic constants of the pure transverse C T = (C 11 − C 12 )/2 in (a) and C 44 in (b) of one other clathrate R 3 Pd 20 Ge 6 .…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, the result obtained by Nakanishi shows a slight increase around 30 K, however, no apparent frequency dependence was found so far. 21 These results probably lead to the absence of rattling in CeOs 4 Sb 12 though the work is still continuing and support the idea that the contribution of conduction electrons is essential for the development of rattling through electron-phonon interaction. Figure 2 displays the temperature dependence of the relative change in elastic constants of the pure transverse C T = (C 11 − C 12 )/2 in (a) and C 44 in (b) of one other clathrate R 3 Pd 20 Ge 6 .…”
Section: Resultsmentioning
confidence: 87%
“…The AFQ ordering seems incompatible with the elastic constant in H ʈ ͓001͔, which shows no clear anomaly at T ‫ء‬ in high magnetic fields. 21 Meanwhile, a recent angleresolved specific-heat study revealed that the specific-heat anomaly at T ‫ء‬ is markedly suppressed in the case of H ʈ ͓001͔, in comparison with other field directions. 31 Therefore, elastic constant measurements in magnetic fields applied along the other field directions are necessary in order to discuss quadrupole interactions in high magnetic fields.…”
Section: B Possible High-field Ordered Statementioning
confidence: 99%
“…Moreover, specific-heat, resistivity, elastic constant, and the 1 / ͑T 1 T͒ anomalies at T ‫ء‬ become less distinctive with increasing magnetic field. 7,12,17,21 Thus, further investigations by means of microscopic probes are required to elucidate the nature of the unusual state at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Different combinations of Ce‐filled skutterudites have been reported in the literature. For example, electronic, optical, and transport properties of CeRu 4 Sb 12 have been studied by many researchers but their reported results are not consistent because it has been reported having semi‐metallic character, the metallic character with a pseudo‐gap of 0.09 eV, and semi‐conducting nature . Whereas CeRu 4 P 12 has been reported as a semiconductor with indirect band‐gap and CeFe 4 Sb 12 has been reported as semiconductor .…”
Section: Introductionmentioning
confidence: 99%